2013
DOI: 10.1158/1078-0432.ccr-12-3235
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy with or without Zoledronic Acid in Early Breast Cancer—A Randomized Biomarker Pilot Study

Abstract: Purpose: To investigate the short-term biologic effects of neoadjuvant chemotherapy þ/À zoledronic acid (ZOL) in invasive breast cancer.Experimental Design: Forty patients were randomized to receive a single 4 mg infusion of ZOL 24 hours after the first cycle of FE 100 C chemotherapy, or chemotherapy alone. Randomization was stratified for tumor stage, ER, HER2, and menopausal status. All patients had repeat breast core biopsy at day 5 (D5) AE day 21 (D21). Effects on apoptotic index, proliferation (Ki67), gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
15
1
1
Order By: Relevance
“…likelihood of stabilized or improved cognition or lack of worsening in cognition in that specific individual) such a marker could conceivably be introduced as a surrogate biomarker for the primary outcome rather than change in cognition after appropriate validation work and ongoing discussions with regulators. Recent work suggests that early change in plasma S100β and neuron specific enolase (NSE) may predict six month clinical outcomes in stroke patients[63] and this area has been studied extensively in cancer[6466]. The ideal situation would be the identification of such a response biomarker that changes within six months (given a specific profile of study subjects included in the cohort at the beginning), thereby significantly decreasing the time of the clinical trials.…”
Section: Placing Blood-based Biomarkers Into a Broader Contextmentioning
confidence: 99%
“…likelihood of stabilized or improved cognition or lack of worsening in cognition in that specific individual) such a marker could conceivably be introduced as a surrogate biomarker for the primary outcome rather than change in cognition after appropriate validation work and ongoing discussions with regulators. Recent work suggests that early change in plasma S100β and neuron specific enolase (NSE) may predict six month clinical outcomes in stroke patients[63] and this area has been studied extensively in cancer[6466]. The ideal situation would be the identification of such a response biomarker that changes within six months (given a specific profile of study subjects included in the cohort at the beginning), thereby significantly decreasing the time of the clinical trials.…”
Section: Placing Blood-based Biomarkers Into a Broader Contextmentioning
confidence: 99%
“…Patients completed assessments of psychosocial and quality-of-life variables and blood samples were drawn to measure serum markers of disease. Blood serum has been shown to undergo changes after chemotherapy treatment (Winter et al 2013), so patients who had undergone chemotherapy were excluded from our analysis because of the potential impact of the medications on serum markers. The present study was a part of a larger study investigating the association between psychological factors and survival (Cohen et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analysis of individual patient data from randomised trials of adjuvant BP use in early breast cancer has further proved a reduction in the risk of bone and other metastases and breast cancer mortality only in older or oestrogen-deprived patients [35]. Two prospective clinical studies [36,37] explored the anti-tumour potential of ZOL in the neoadjuvant setting. The first study by Winter and colleagues [36] showed a synergistic effect of ZOL treatment followed by chemotherapy possibly due to an increased apoptosis and reduced proliferation and a reduction of the VEGF levels.…”
Section: Table 1 Bisphosphonate Classes and Their Anti-tumour And/ormentioning
confidence: 99%
“…Two prospective clinical studies [36,37] explored the anti-tumour potential of ZOL in the neoadjuvant setting. The first study by Winter and colleagues [36] showed a synergistic effect of ZOL treatment followed by chemotherapy possibly due to an increased apoptosis and reduced proliferation and a reduction of the VEGF levels. The second study [37], enrolling fifty-three breast cancer patients (thirty-three with locally advanced and twenty with a first bone-only relapse) demonstrated that a single 4mg dose of ZOL 14 days prior to any further treatment increased the number of apoptotic CTCs and primary tumour cells, reduced tumour and endothelial cell proliferation.…”
Section: Table 1 Bisphosphonate Classes and Their Anti-tumour And/ormentioning
confidence: 99%